Increased extracellular polymeric substances production contributes for the robustness of aerobic granular sludge during long-term intermittent exposure to 2-fluorophenol in saline wastewater. (April 2021) - Oliveira, Ana S.; Amorim, Catarina L.; Mesquita, Daniela P.; Ferreira, Eugénio C.; van Loosdrecht, Mark; Castro, Paula M.L.
Graphical abstract: Highlights: Lab-scale AGS-SBR intermittently fed with 2-fluorophenol and NaCl. Ammonium removal impaired by 2-FP, but reestablished when 2-FP feeding ceased. Phosphate removal recovered after the initial exposure to stress conditions. Increased EPS production in later phases in responding to stress shocks. Stressors had more immediate effects on nutrients removal than on EPS production. Abstract: Industrial effluents often contain organic pollutants and variable salinity levels, making their treatment challenging. The high content of extracellular polymeric substances (EPS) in the aerobic granular sludge (AGS) is thought to protect the microbial communities from stressful conditions. Ammonium and phosphate removal, EPS production, and granular morphology were assessed in a lab-scale AGS reactor operated during 138 days at continuous low or moderate salinity levels (1.41–6.46 g/L of NaCl) and intermittent short-term loadings of a fluoroorganic pollutant, 2-fluorophenol (2-FP, 20 mg/L). 2-FP was not degraded throughout operation. Ammonium removal efficiency was drastically affected whenever 2-FP stressor was present, decreasing from 99 % to non-detectable conversion levels, but completely recovering after 2-FP feeding ceased. Phosphate removal, initially disturbed by exposure to stress conditions, recovered with time, even when stressors were still present. Complete phosphate removal did not occur in periods when nitrite temporarily accumulated after nitrification started to recover. EPS composition and concentration in AGS varied during operation, initially decreasing from 133 to 34 mg/g VSS of AGS, during the stress phases but recovering thereafter to 176 mg/gVSS of AGS . Breakage of granules into smaller ones occurred at two different operational moments due to stressors presence. The presence of 2-FP and moderate salinity levels in wastewater had more immediate detrimental effects on nutrients removal than on EPS production. The AGS system capacity to recover the nutrient removal performance and EPS production, after the withdrawal of 2-FP from the inlet stream reinforced its robustness to deal with industrial wastewaters.